Steroid resistant bullous pemphigoid induced by pembrolizumab in a patient with metastatic lung adenocarcinoma: case report and review of the literature - Elie S. Bterrani; Francois G. Kamar (Discover Oncology)
Abstract Background Pembrolizumab, a PD-1 inhibitor, is widely used for treating advanced cancers, including metastatic non-small cell lung cancer (NSCLC). However, its use can lead to immune-related adverse events (IRAEs), including cutaneous manifestations such as bullous pemphigoid (BP). Case presentation We report a case of a 69-year-old gentleman with metastatic left lung adenocarcinoma who developed steroid-resistant BP following pembrolizumab treatment. Initially diagnosed in August 2020 and treated with surgery, chemotherapy, and an IL-1B inhibitor, the patient showed no evidence of recurrence until November 2021. Subsequent metastases were treated with surgery, stereotactic radiosurgery (SRS), and whole-brain radiotherapy (WBRT). In November 2022, pembrolizumab was initiated. Following three sessions, the patient developed facial skin edema, muscle weakness, and later, a rash with multiple bullae. Despite discontinuing pembrolizumab and starting high-dose topical steroids and oral prednisone, the BP proved to be  refractory. The patient was switched to methotrexate with marked improvement but not complete resolution. Continued management included reduced pembrolizumab doses and additional SRS, eventually achieving control over both the metastatic disease and BP. Discussion This case highlights a case of severe and steroid-resistant nature of pembrolizumab-induced BP, necessitating alternative immunosuppressive therapy. The complexity of managing IRAEs in patients undergoing ICI therapy underscores the importance of a multidisciplinary approach and vigilant monitoring. Conclusion This report adds to the growing body of evidence on IRAEs, particularly BP induced by ICIs, and suggests that methotrexate can be an effective treatment for steroid-resistant BP in the context of cancer immunotherapy. Further research is needed to better understand the mechanisms and optimal management strategies for ICI-induced BP.